Managing technological innovation - Twiss, Brian C. (Longman, 1974)
The management of technological innovation is both an art, as well as a science; the process involves the know-how and technological core skills to deliver the functionality on the one hand, and (with an ear on the ground) the ability to identify changes in technologies to come up with new innovations on the other. This requires, as a result, frameworks, system tools, and methodologies to improve the yield in innovations.